80.1k views
15 votes
What is the solution to the equation the sqaure root of 5x -7 = the sqaure root of 3x + 5

User Copilot
by
6.1k points

2 Answers

3 votes

Answer:

x = 6

Explanation:


√(5x - 7) =
√(3x +5) ( square both sides to clear the radicals )

5x - 7 = 3x + 5 ( subtract 3x from both sides )

2x - 7 = 5 ( add 7 to both sides )

2x = 12 ( divide both sides by 2 )

x = 6

User Miles Budnek
by
5.5k points
3 votes

Answer:

  • x = 6

Explanation:

If you square both sides you get:

  • 5x - 7 = 3x + 5

Solve it for x:

  • 5x - 3x = 5 + 7
  • 2x = 12
  • x = 6
User Amr
by
5.2k points